Sun, Wind and Light (Design Strategies in Consistent Architecture with Climate) Case Study: Yazd City - alireza entezari; fatemeh mayvaneh; froogh khazaeenejad (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this research is to study the comfort conditions and determine the best measures for design and architecture compatible with the climate in Yazd. In this regard, the climatic data of Yazd city has been used in EPW format during the period (1981-2017). The results of the study of temperature and relative humidity also showed that temperatures of more than 38 ° C are visible in June and July. This suggests the need for a shadow in the architecture of the climate. In July, the discomfort conditions prevail over the entire day. From June to October (midday to midnight), midnight hours due to low humidity (38%) and high temperatures, conditions of discomfort and drought are very visible. The highest humidity is in the cold months of the year. In the wind hours of February to May (February to April), there is a discomfort. Also, according to the overall radiation pattern at different hours of the day, it was also shown that 25% of the daylight hours is very high and non-comfort, and 8% are in comfort conditions, which is more related to the cold weather of the year and the early hours And the end of the day. In general, due to the climate of Yazd city and the results of analysis, 20 strategies for architectural design have been used.